Circular RNA circPTPRF promotes the progression of GBM via sponging miR-1208 to up-regulate YY1 - Zhou, Jiang; Wang, Chengbin; Liu, Yingliang; Cui, Daming; Wang, Zhenlin; Jiang, Yang; Gao, Liang (Cancer cell international, 2022)
Glioblastoma (GBM) is the most common primary malignant tumor in the brain, and its robust proliferation and invasion abilities reduce the survival time of patients. Circular RNAs (circRNAs) play an essential role in various tumors, such as regulating tumor cell proliferation, apoptosis, invasion, metastasis, and other progressive phenotypes through different mechanisms. Finding novel circRNAs may significantly contribute to the prognosis of GBM and provide the basis for the targeted therapy of GBM. In this study, we found circPTPRF is a novel circRNA that has never been studied, which was highly expressed in GBM and is closely related to poor patient prognoses. After knockdown or overexpression in glioma cell lines (U87 and LN229) and glioma stem cells (GSCs), we identified that circPTPRF could promote proliferation, invasion, and neurospheres formation abilities of GBM via in vitro and in vivo experiments. Mechanisms, miR-1208 was confirmed as a target of circPTPRF, and miR-1208 can also target the 3’UTR of YY1, and they were proved by luciferase reporter, western blotting (WB), qPCR and RNA immunoprecipitation (RIP) assays. The following rescue experiments demonstrated that circPTPRF was a miR-1208 sponge for upregulating YY1 expression to promote proliferation, invasion and neurosphere formation abilities of GBM in vitro. In conclusion, the circPTPRF/miR-1208/YY1 axis can regulate GBM progression. CircPTPRF may play an essential role in GBM diagnosis and prognostic prediction and be an important molecular target for GBM therapy.